Wearable low-cost inertial sensor-based electrogoniometer for measuring joint range of motion (2017)
Human movement analysis have become fundamental for a wide range of applications, such as physical therapies, neuro-rehabilitation, sports medicine, human motor system performance assessment and occupational medicine. This paper focuses on the design, implementation and validation of an inertial sensor-based portable electrogoniometer aimed at measuring joint range of motion. The system is composed of two inertial measurement units and a microcontroller that permits real-time human motion capture. The electrogoniometer was tested both in static and dynamic conditions in comparison to a standard commercial electrogoniometer during elbow movements. For static validation, the concordance correlation coefficient (ρC) obtained was 0.9605. The ρC found for slow-speed cyclical movements was 0.9830 and the ρC found for moderate-speed cyclical movements was 0.9619.